2014
DOI: 10.1103/physrevlett.112.023905
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Anderson Localization of Light in a Random Ensemble of Point Scatterers

Abstract: As discovered by Philip Anderson in 1958, strong disorder can block propagation of waves and lead to the localization of wavelike excitations in space. Anderson localization of light is particularly exciting in view of its possible applications for random lasing or quantum information processing. We show that, surprisingly, Anderson localization of light cannot be achieved in a random three-dimensional ensemble of point scattering centers that is the simplest and widespread model to study the multiple scatteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
313
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(344 citation statements)
references
References 38 publications
23
313
1
1
Order By: Relevance
“…Basing on the above arguments, John [33,34] has concluded that, in contrast to the electronic disordered systems, the light cannot be localized in diffusively scattering and fully disordered medium. This qualitative conclusion is confirmed by more precise recent considerations [40] accounting the vector nature of light.…”
Section: Such a Phenomenon Of Trapping Of Electrons In Disordered Matsupporting
confidence: 71%
“…Basing on the above arguments, John [33,34] has concluded that, in contrast to the electronic disordered systems, the light cannot be localized in diffusively scattering and fully disordered medium. This qualitative conclusion is confirmed by more precise recent considerations [40] accounting the vector nature of light.…”
Section: Such a Phenomenon Of Trapping Of Electrons In Disordered Matsupporting
confidence: 71%
“…Two such examples are the Anderson localization of light [55] and CBS, which we here discuss. Finally, we note that (16) describes the light in a scalar approximation, which is a good approximation at low atomic density [56,57]. This limit is relevant to the experiments described in [30][31][32][33].…”
Section: Coherent Backscatteringmentioning
confidence: 99%
“…These methods, whether called classicalelectrodynamics simulations or coupled-dipole simulations, are now a routine theoretical tool [2,4,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. Closely related numerical techniques based on the analysis of the eigenstates of the coupled system of the light and the atoms [15,[27][28][29][30][31][32] or density matrices and quantum trajectories [33][34][35] are also widely used today. Other ideas drawn from the theory of radiative transfer [36,37] and multiple scattering [38,39], enhanced with numerics, also have potential to make inroads into the questions about light propagation in atomic media [40].…”
Section: Introductionmentioning
confidence: 99%